ANALYSIS OF TRAFFIC WHEN SYSTEMATIZING INFORMATION FLOWS IN LAN LOGISTICS: ANALYSIS OF TRAFFIC WHEN SYSTEMATIZING INFORMATION FLOWS IN LAN LOGISTICS - Kazakov, Stefan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The paper presents research of the traffic when systematizing information flows in logistics. Ethernet is one of the most popular networks, especially if equal access networks are to be built and maintained. Ethernet is widely used to control machines, production lines and even entire production plants. However, working in real-time mode sometimes creates conflicts in certain actuators which are time-sensitive to the commands sent to them. Therefore, it is necessary to investigate the average delay time and time dispersion of the LAN Ethernet, to be able to meet the requirements for real-time operation in logistics.